Christ in the Limelight: Contemporary Films and Christological Discourse. (March 2014) - Guðmundsdóttir, Arnfríður
Abstract The aim of this article is to show how theology can, through the medium of film, engage contemporary interpretations of Jesus' person and work. Starting out by tracing the development taking place in films about Jesus throughout the twentieth century, the focus then moves to a theological reading of Mel Gibson's interpretation of the passion story for the twenty‐first century in his movie The Passion of the Christ.